It can't go on forever: the implications of the global grab for declining fish stocks (Green Peace International AmsterdamNL, 1993)
Highlights the dangers of over fishing which is destroying not only the commercially forgotten fish population, but also a vast array of other marine wildlife species in the process.
DC